Vented gas explosion in a cylindrical vessel with a relief pipe - Mohd. Kasmani, Rafiziana; Andrews, G. E.; Phylaktou, H. N.; Willacy, S. K. (Penerbit UTM Press, 2009)
A study of vented explosions in length/diameter (L/D) of 2 of cylindrical vessel with a duct pipe (L/D = 6) is reported. The influence of vent burst pressure and ignition locations on maximum overpressure generated inside the vessel, flame speeds and unburnt gas velocities ahead of the flame were systematically investigated. Propane and methane-air mixtures with equivalence ratio, ? of 0.8 to 1.6 have been used. Results show that rear ignition exhibits higher maximum overpressures and flame speeds in comparison to central ignition. It is confirmed that prior to the flame entry to the duct, the flow is chocked due to the sonic flow created at the duct entrance.